Instruct Students to Use software to Learn Japanese Language in order to Reach an Advanced Level after Graduation - Huynh Tan Hoi (International Journal of Advanced Science and Technology, 2020)
Considered as one of the hardest languages in the world, however, Japanese is still the language that many young people choose to learn. Today, with the development of technology, learning foreign languages in general and Japanese language in particular is not an impossible barrier. Learning materials are not only from paper books, songs but also through software programs of smartphones or computers. Especially, students who begin to explore effective skills to study this language need to access modern technologies to improve their learning much better. When using the software, some students may feel embarrassed and challenged but everything would go smoothly after a few days. After completing the course, students will get more knowledge; achieve a higher knowledge such as N2 or N1 Japanese Language Proficiency Test Certificate. In this research paper, 100 students who are studying at Ho Chi Minh City FPT University were asked to complete the questionnaire at the beginning of May up to August of 2018. Through this research, we realize that with the guidance of lecturers, the necessity of using modern software is indispensable in term of improving quality of teaching and learning process.